3‐photon fluorescence imaging of sulforhodamine B‐labeled elastic fibers in the mouse skin in vivo. Issue 11 (17th July 2019) - He, Chen; Gan, Mengyao; Deng, Xiangquan; Liu, Hongji; Qiu, Ping; Wang, Ke
Abstract: Elastic fibers are key constituents of the skin. The commonly adopted optical technique for visualizing elastic fibers in the animal skin in vivo is 2‐photon microscopy (2 PM) of autofluorescence, which typically suffers from low signal level. Here we demonstrate a new optical methodology to image elastic fibers in animal models in vivo: 3‐photon microscopy (3 PM) excited at the 1700‐nm window combining with preferential labeling of elastic fibers using sulforhodamine B (SRB). First, we demonstrate that intravenous injection of SRB can circumvent the skin barrier (encountered in topical application) and preferentially label elastic fibers, as verified by simultaneous 2 PM of both autofluorescence and SRB fluorescence from skin structures. Then through 3‐photon excitation property characterization, we show that 3‐photon fluorescence can be excited from SRB at the 1700‐nm window, and 1600‐nm excitation is most efficient according to our 3‐photon action cross section measurement. Based on these results and using our developed 1600‐nm femtosecond laser source, we finally demonstrate 3 PM of SRB‐labeled elastic fibers through the whole dermis in the mouse skin in vivo, with only 3.7‐mW optical power deposited on the skin surface. We expect our methodology will provide novel optical solution to elastic fiber research. Abstract : This study demonstrates the labeling and multiphoton imaging of elastic fibers in mouse skin in vivo. Intravenous injection of SRB preferentially labels elastic fibers in mouse skin. Quantitative measurement shows 3‐photon fluorescence can be generated from SRB excited at the 1700‐nm window, promising for deep‐tissue 3‐photon microscopy. in vivo 3‐photon fluorescence microscopy shows that elastic fibers through the whole mouse skin can be imaged with only 3.7 mW optical power.